Severe lupus nephritis in the present days - Moroni, Gabriella; Calatroni, Marta; Ponticelli, Claudio (Frontiers in Nephrology, 2022)
Lupus nephritis (LN) is one of the most frequent and severe organ manifestations of systemic lupus erythematosus (SLE) that is a chronic autoimmune disease. Despite improvement in patient and renal prognosis, the disease continued to be associated with a high rate of end stage kidney disease. Along the last decades, it seems that the epidemiology of LN and its clinical presentation have progressively changed. The forms with renal insufficiency at presentation seem to have progressively reduced in developed countries in favour of more mild clinical presentations with urinary abnormalities only. To this clinical change does not correspond a less severe histological lesions, in fact, the extent of active lesions at kidney biopsy are unchanged, whereas chronic lesions are becoming less frequent and less severe. Meanwhile, new types of severe LN defined by the variable association of demographic, clinical, histological characteristics at diagnosis or during the follow-up are gradually emerging and require attention in assessing the therapy and prognosis. During the last years, randomized controlled trials have reported the efficacy of new drugs in association with standard therapy to improve the rate of short- and medium-term renal response. One of the advantages is that these results were obtained with reduced dosage of corticosteroids whose protracted use is associated with increase of chronic organ damage. Optimization of therapeutical strategies, tailored on the demographic clinical and histological characteristics, with combination of old and new drugs are urgently needed for severe LN.